2013
DOI: 10.1016/j.jval.2013.08.759
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Indication Extensions on Pharmaceutical Prices

Abstract: A455cost benefit analysis and 3 BIAs. Key assessment criteria that the other studies did not meet were consideration of all relevant costs and execution of a sensitivity analysis. Of the best quality studies, 3 reported net economic benefits from implementing SEDs, at least in the base case analysis. ConClusions: Investment in SEDs generates economic benefits from savings in managing medical sharps injuries and their sequelae. Future economic evaluations need to carefully assess all important and pertinent cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed, previous research showed that orphan drug prices are determined based on the prevalence of the first indication [ 36 , 45 ]. Launch prices for the first indication are unlikely to be reviewed following approval in other indications [ 46 ]. We calculated that orphan drugs with multiple indications have a significantly larger potential market size, although it is essential to bear in mind that no correct estimates of prevalence exist and not all patients are diagnosed and/or treated [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research showed that orphan drug prices are determined based on the prevalence of the first indication [ 36 , 45 ]. Launch prices for the first indication are unlikely to be reviewed following approval in other indications [ 46 ]. We calculated that orphan drugs with multiple indications have a significantly larger potential market size, although it is essential to bear in mind that no correct estimates of prevalence exist and not all patients are diagnosed and/or treated [ 47 ].…”
Section: Discussionmentioning
confidence: 99%